2017
DOI: 10.1007/s00572-017-0771-2
|View full text |Cite
|
Sign up to set email alerts
|

Indirect interactions between arbuscular mycorrhizal fungi and Spodoptera exigua alter photosynthesis and plant endogenous hormones

Abstract: Peanut (Arachis hypogaea Linn. cv: Luhua 11) and tomato (Lycopersicon esculentum Mill. cv: Zhongshu 4) were inoculated with arbuscular mycorrhizal fungi (AMF) Funneliformis mosseae BEG167 (Fm), Rhizophagus intraradices BEG141 (Ri), and Glomus versiforme Berch (Gv), and/or Spodoptera exigua (S. exigua) under greenhouse conditions. Results indicated that feeding by S. exigua had little influence on colonization of peanut plants by AMF, but improved colonization of tomato by Fm and Gv. Feeding by S. exigua had li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
37
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 37 publications
8
37
0
4
Order By: Relevance
“…The general increase in foliar cardenolides mediated by AMF was not a simple consequence of improved plant nutrition; there were no clear associations between cardenolide expression and either foliar nutrient concentrations or plant biomass. Instead, AMF inoculation may have increased defense metabolites through interactions with phytohormonal signaling pathways (García- Garrido et al 2002, Jung et al 2012, Song et al 2013, He et al 2017. The induction of cardenolides in milkweeds is related to bursts in JA concentrations .…”
Section: Effects Of Amf and Herbivores On Aboveground Defensesmentioning
confidence: 99%
See 3 more Smart Citations
“…The general increase in foliar cardenolides mediated by AMF was not a simple consequence of improved plant nutrition; there were no clear associations between cardenolide expression and either foliar nutrient concentrations or plant biomass. Instead, AMF inoculation may have increased defense metabolites through interactions with phytohormonal signaling pathways (García- Garrido et al 2002, Jung et al 2012, Song et al 2013, He et al 2017. The induction of cardenolides in milkweeds is related to bursts in JA concentrations .…”
Section: Effects Of Amf and Herbivores On Aboveground Defensesmentioning
confidence: 99%
“…Plant responses to herbivore feeding are also shaped by interactions with belowground microbial symbionts, such as arbuscular mycorrhizal fungi (AMF) , Kempel et al 2010, Babikova et al 2014, Wang et al 2015, Minton et al 2016, He et al 2017. AMF colonize the roots of over 80% of plant species globally and provide nutrients and water to plants in exchange for sugars (Wang and Qiu 2006, Smith and Read 2008, Soudzilovskaia et al 2015.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meloidogyne incognita ) and tomato disease development. Recently, He et al (2017) reported that AM fungi and their indirect interactions with insect ( Spodoptera exigua ) altered the photosynthesis and plant endogenous hormones of peanut and tomato. Additionally, the application of mycorrhizal inoculation was found to improve carbon sequestration of coalfield soils and thus to be beneficial for the ecological reclamation in mine region (Wang et al 2016b).…”
Section: Mycorrhizal Functionmentioning
confidence: 99%